Diffuse and bilateral lichen striatus. - Bellosta, M.; Baldini, F. (European Journal of Pediatric Dermatology, 1999)
Lichen striatus is a rare, linear, inflammatory skin disorder, which is due to not well defined causes. Lichen striatus usually appears in the first decade, more frequently in females, and spontaneously regresses within a few months. Its typical linear and mosaic distribution is due to a preexisting gene mutation, which is not phenotypically evident. The latter is unveiled by an exogenous, probably viral factor. Here is reported a 3-year-old little girl, affected from the age of 8 months by diffuse and bilateral lichen striatus.